Comparative evaluation of interfaces for presenting location-based information on mobile devices - Goh, Dion Hoe-Lian (2012)
Location-based information can now be easily accessed on mobile devices and is commonly presented in the form of lists of items, maps and more recently, augmented reality (AR). Each approach (list, map, AR) has its strengths and weaknesses. In this paper, we investigate the three approaches for searching and browsing location-based information, taking into account performance and users’ perceptions of usability. Participants were issued with Android smartphones pre-loaded with a specific interface and performed a set of browsing and searching tasks. Results suggest that all three interfaces performed similarly for search tasks, but for browsing, the map performed worst. In terms of usability, participants appeared to rate the list better than the other interfaces for presentation location-based information.